2018
DOI: 10.1016/j.jaapos.2017.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Visual acuity recovery following traumatic hyphema in a pediatric population

Abstract: There is good potential for visual recovery following uncomplicated traumatic hyphema in children. In our patient cohort, the majority of patients had significant improvement in visual acuity within the first 28 days; in some children visual acuity continued to improve beyond the first month.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 9 publications
2
18
2
Order By: Relevance
“…Acutely elevated IOP and angle recession were common complications in our study cohort. Postinjury IOP elevation >21 mm Hg was noted in approximately 50% of our study patients, slightly higher than that reported in a similar population,7 11 and IOP typically peaked within 2 weeks of injury. Although several patients required surgery, most surgeries were not directly related to their hyphaema.…”
Section: Discussioncontrasting
confidence: 70%
See 3 more Smart Citations
“…Acutely elevated IOP and angle recession were common complications in our study cohort. Postinjury IOP elevation >21 mm Hg was noted in approximately 50% of our study patients, slightly higher than that reported in a similar population,7 11 and IOP typically peaked within 2 weeks of injury. Although several patients required surgery, most surgeries were not directly related to their hyphaema.…”
Section: Discussioncontrasting
confidence: 70%
“…Closed-globe traumatic hyphaema in children has a favourable visual prognosis 7. Although the great majority of patients (83%) in our study had a final visual acuity of 0.30 logMAR (20/40) or better, a minority (17%) fared more poorly.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…5 To prevent the complications of the hyphema, frequent follow-up visits to the ophthalmologist are necessary during the subsequent weeks. 6 As trauma during sports is the major cause of…”
Section: What Is the Diagnosis?mentioning
confidence: 99%